The effect of change management and organisational culture on junior high school teacher performance - Yannizar Yannizar; Elna Hasmita; Zahrun Zahrun; Adiromi Adiromi; Verry Irfan (Institute of Computer Science (IOCS), 2023)
SMP Negeri 8 Sungai Penuh is one of the educational institutions that always try to improve the quality of education. Therefore teachers have an important role in improving the quality of education. However, teacher performance at SMP Negeri 8 Sungai Penuh is still low. Several factors influence the low performance of SMP Negeri 8 Sungai Penuh teachers, namely change management and organizational culture. This research aims to determine the influence of change management and organizational culture on teacher performance at SMP Negeri 8 Sungai Penuh. The type of this research is quantitative. The sample used in this research was 32 teachers at SMP Negeri 8 Sungai Penuh. The data collection techniques were questionnaires, observation, documents, and interviews. Data were analyzed using multiple linear analysis with the help of SPSS. The research shows that change management has a significant effect on teacher performance at SMP Negeri 8 Sungai Penuh. Organizational culture also influences teacher performance at SMP Negeri 8 Sungai Penuh. Simultaneously, change management and organizational culture have a significant effect on teacher performance at SMP Negeri 8 Sungai Penuh.